Foresight modeling to inform decision making for agricultural development and food security - Wiebe, Keith (2016)
IFPRI Senior Research Fellow Keith Wiebe’s presentation at the third Global Conference on Agricultural Research for Development (GCARD3). For more information, please visit: https://www.ifpri.org/event/third-global-conference-agricultural-research-development